PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS II C SEKOLAH DASAR NEGERI 169 PEKANBARU - Dona, Exmela (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Astract: Pursuant to perception of early writer at study of IPS of student of class of II C SDN 169 Pekanbaru, that lowering result of learning student because of previous teacher still use the discourse method. Data of early result learn from 44 student people with the class mean 70 only 15 student (34%) a success reach the KKM specified is 75. Subject Research is student of Class of II C SD N 169 Pekanbaru at even semester of school year 2014/2015 with the student amount 44 people consisted of the men 24 people and woman 20 people. Design Research in the form of Research of class action (PTK). This Research Procedure is consisted of four activity phase of every cycle, and this research is executed as much 2 cycle. One cycle composed and 2 multiply the meeting and 1 multiplies the Daily Restating (UH). Research Instrument consisted of the research peripheral that is Syllabus, RPP and LKS. While instrument of data collecting that is Sheet of activity observation learn and student and problem test of result of learning. Data analysis used by a technique descriptively in the form of activity learn and student, result of learning student, Rule Classical and Analyze the make-up of result learn. Result of this research showing that applying model the direct study can improve the result learn the IPS of student of class of II C SD N 169 Pekanbaru, seen from make-up of result learn the student from elementary score to cycle I with the class mean is 70 improving 15,10% becoming 80,57. Cycle I to cycle II improve 8,18% becoming 87,16. As a whole from elementary score to cycle II mount equal to 34,51%. Activities learn and student experience of the improvement at every cycle. Activities learn at cycle I percentage is 80% mounting as much 12,5% becoming to become 90% at cycle II. Student Activity at cycle I percentage is 80% mounting as much 12,5% becoming to become 90% at cycle II.Keyword: Applying Model the Direct Study. Result Learn the IPS Student